2020
DOI: 10.1016/j.injury.2019.10.079
|View full text |Cite
|
Sign up to set email alerts
|

An explorative, biomechanical analysis of spine motion during out-of-hospital extrication procedures

Abstract: Objectives: The extrication of patients following a road traffic collision is among the basic procedures in emergency medicine. Thus, extrication is a frequently performed procedure by most of the emergency medical services worldwide. The appropriate extrication procedure depends on the patient's current condition and accompanying injuries. A rapid extrication should be performed within a few minutes, and the cervical spine (at least) should be immobilized. To our knowledge, the scientific literature and curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 29 publications
1
19
0
2
Order By: Relevance
“…Such a finding would also have significant implications for recommendations to bystander / buddy care at the scene of a motor vehicle collision. In our study there was a strong association between collar use and decreased cervical spinal movement (p < 0.001); this finding is in keeping with the intended purpose of such devices and is consistent with previous work [25,33]. It is contrary to the findings of Dixon et al who identified a small, mean increase in movement associated with collars when degrees of anterior-posterior, medial-lateral and rotational movement were combined [23].…”
Section: Cervical Collarssupporting
confidence: 92%
See 3 more Smart Citations
“…Such a finding would also have significant implications for recommendations to bystander / buddy care at the scene of a motor vehicle collision. In our study there was a strong association between collar use and decreased cervical spinal movement (p < 0.001); this finding is in keeping with the intended purpose of such devices and is consistent with previous work [25,33]. It is contrary to the findings of Dixon et al who identified a small, mean increase in movement associated with collars when degrees of anterior-posterior, medial-lateral and rotational movement were combined [23].…”
Section: Cervical Collarssupporting
confidence: 92%
“…Data from a total of 392 extrications were successfully collected for analysis (98% data capture success rate). Seven of the ten participants were female, with a mean age across all of the participants of 39 years (range 21-59) and BMI of 25.1 (range [19][20][21][22][23][24][25][26][27][28][29].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, the remaining flexion and the remaining lateral bending of the immobilized cervical spine were measured with a wireless human motion tracker system (Xsens Technologies, Enschede, Netherlands). Compared to other methods, this measurement method with a motion tracker has been proven 25 27 and guarantees exact measurement results 28 . The endpoints of the measurements were maximal flexion and maximal lateral bending.…”
Section: Methodsmentioning
confidence: 99%